If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -9y = 27 Solving 9x + -9y = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9y' to each side of the equation. 9x + -9y + 9y = 27 + 9y Combine like terms: -9y + 9y = 0 9x + 0 = 27 + 9y 9x = 27 + 9y Divide each side by '9'. x = 3 + y Simplifying x = 3 + y
| f(x)=10x-18 | | 4x^2+x-44=0 | | 50-(30+80)= | | u-v+6u-3v= | | (3x-4)(x-20)=3x(x-9)-3 | | 2-3(7x+9)=6 | | 5n^2+n-5=0 | | N+4=3n+16 | | -5t^2+40t+20= | | 0.2r-1.3r+0.6=-0.9+3.6 | | 19/2/3 | | 2/3/18 | | 2k+2=-13+3k | | X+0.6x+0.03x=500 | | 1/5-1/6z=7/6 | | N-9=9+15 | | 4(3z+5)=10-2(z-5) | | 121^-1/2 | | 426=350t | | 2(1-7y)=4y+3 | | T-5+7+2k-3k=k-8 | | 6y+7=10y-3 | | 462=370x | | (36x^2y^4)^1/2 | | 4(3z-1)-3(z-8)=3(z-1) | | (T-2)/(4-t) | | -9+10x=4x+15 | | 9=12x^2-23x | | -77.08=9.4y | | 2x-1-4=0 | | -0.56m=4.592 | | 2.3x=14.582 |